Diacylglycerol Lipase α Knockout Mice Demonstrate Metabolic and Behavioral Phenotypes Similar to Those of Cannabinoid Receptor 1 Knockout Mice - Powell, David R.; Gay, Jason P.; Wilganowski, Nathaniel; Doree, Deon; Savelieva, Katerina V.; Lanthorn, Thomas H.; Read, Robert; Vogel, Peter; Hansen, Gwenn M.; Brommage, Robert; Ding, Zhi-Ming; Desai, Urvi; et al. (Frontiers in Endocrinology, 2015)
After creating >4650 knockouts (KOs) of independent mouse genes, we screened them by high-throughput phenotyping and found that cannabinoid receptor 1 (Cnr1) KO mice had the same lean phenotype published by others. We asked if our KOs of DAG lipase a or b (Dagla or Daglb), which catalyze biosynthesis of the endocannabinoid (EC) 2-Arachidonoylglycerol (2-AG), or Napepld, which catalyzes biosynthesis of the EC anandamide, shared the lean phenotype of Cnr1 KO mice. We found that Dagla KO mice, but not Daglb or Napepld KO mice, were among the leanest of 3651 chow-fed KO lines screened. In confirmatory studies, chow- or high fat diet-fed Dagla and Cnr1 KO mice were leaner than wild type (WT) littermates; when data from multiple cohorts of adult mice were combined, body fat was 47% and 45% lower in Dagla and Cnr1 KO mice, respectively, relative to WT values. In contrast, neither Daglb nor Napepld KO mice were lean. Weanling Dagla KO mice ate less than WT mice and had body weight similar to pair-fed WT mice, and adult Dagla KO mice had normal activity and VO2 levels, similar to Cnr1 KO mice. Our Dagla and Cnr1 KO mice also had low fasting insulin, triglyceride and total cholesterol levels, and after a glucose challenge had normal glucose but very low insulin levels. Dagla and Cnr1 KO mice also showed similar responses to a battery of behavioral tests. These data suggest: 1) the lean phenotype of young Dagla and Cnr1 KO mice is mainly due to hypophagia; 2) in pathways where ECs signal through Cnr1 to regulate food intake and other metabolic and behavioral phenotypes observed in Cnr1 KO mice, Dagla alone provides the 2-AG that serves as the EC signal; and 3) small molecule Dagla inhibitors with a pharmacokinetic profile similar to that of Cnr1 inverse agonists are likely to mirror the ability of these Cnr1 inverse agonists to lower body weight and improve glycemic control in obese patients with type 2 diabetes, but may also induce undesirable neuropsychiatric side-effects.